BUSINESS ANALYSIS OF PURSE SEINE FISHING GEAR AT POPOH BEACH FISHING PORT, EAST JAVA - Widan Al Farizi; Mentari Puspa Wardani; Mimit Primyastanto; Supriyadi Supriyadi; Wanda Khuril Maulia; Moh. Ghufron; Moh. Nur Saidus Tsani (Jurnal Perikanan Unram, 2024)
Tuna has an important economic value and is widely favored by people in Tulungagung Regency. According to BPS Kabupaten Tulungagung in 2018-2022 shows a significant increase in the volume and value of production, as well as the number of tuna fishing units. Tuna fishing business using purse seine gear is one of the important sectors in the fishing industry at UPT Pelabuhan Perikanan Pantai Popoh Tulungagung, East Java. This study aims to analyze the financial characteristics of purse seine fishing in the region. The research methods include field surveys, interviews with fishermen, and financial data analysis such as profit, R/C ratio, payback period, NPV, IRR, B/C ratio, and sensitivity analysis. The sampling method used in this research is purposive sampling with a total of 50 respondents. This research was conducted in July 2023. The results of the financial feasibility analysis of fisheries business showed that the average business profit was Rp. 73,811,161 during the tuna season (4 months), the R/C ratio value was 1.37 and the payback period (PP) value was 5.5 years, NPV was Rp. 94,346,195, IRR was 13.2%, B/C ratio was 1.08. The results of the business risk analysis show the coefficient of variation (0.01) < 0.5 and the lower limit of profit (280,898,197) > 0 so that small pelagic purse seine fisheries are included in the category worth developing and avoiding losses or risks suffered are small.